Unlocking the Potential of Multiple Ovulation and Embryo Transfer (MOET) in Water Buffaloes - Nuwasasira, Ronald; Duran, Peregrino G.; Hufana-Duran, Danilda (Journal of Buffalo Science, 2026)
Water buffaloes (Bubalus bubalis) are essential to agricultural economies across Asia and other regions, providing milk, meat, and draught power. Despite their importance, reproductive efficiency remains lower than in cattle due to species-specific constraints, including limited ovarian reserves, poor superovulatory responses, and suboptimal uterine conditions. Multiple Ovulation and Embryo Transfer (MOET) offers a promising strategy for accelerating genetic improvement, particularly in swamp buffalo-dominated areas seeking the infusion of riverine germplasm. While MOET is widely successful in cattle, its application in buffaloes is challenged by anatomical, endocrine, and physiological differences. This review synthesizes current knowledge on MOET development in water buffaloes, highlighting historical milestones, reproductive limitations, protocol refinements, hormonal strategies, embryo recovery innovations, and the role of international collaborations. By addressing biological and logistical barriers, MOET can become a strategic tool to enhance genetic gain, improve reproductive outcomes, and support sustainable buffalo production systems.